Pengembangan Alat dan Panduan Praktikum Densitas Menggunakan Model Pembelajaran Inkuiri Terbimbing Pada Kuliah Fisika Dasar 1 Topik Tekanan Hidrostatis - Marianus, Marianus; Rende, Jeane Cornelda; jurniawati, ni kadek (Universitas Negeri Manado, 2020)
This research is motivated by the absence of tools and guidelines for the density practicum at the Physics Laboratory, UNIMA, so that the practicum activities are not carried out. The purpose of this research is to produce a product of tools and guidelines for practicum density using guided inquiry learning models. This research is a research and development study using the 4 D research model adapted from the Thiagarajan model, which is difine, design, develop and disseminate. The number of students taken is 8 people for the small group test and 16 people for the large group test. The data analysis technique was done descriptively with several types of assessment including cognitive and psychomotor. At the last meeting, students were given a questionnaire to see student responses to density practical tools and guidelines, the results of the questionnaire proved that 97.87% thought that tools and practical guides were very useful (SB) in experimental activities. Based on the results of the study it can be concluded that the product of the tools and guidelines for density practice using guided inquiry learning models with very good and proper qualifications. Keywords: Practicum Guide, Research and Development, Hydrostatic Pressure,